2023
DOI: 10.3233/jpd-223519
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament Light Protein Predicts Disease Progression in Idiopathic REM Sleep Behavior Disorder

Abstract: Background: Idiopathic rapid eye movement sleep behavior disorder (iRBD) is increasingly recognized as a manifestation preceding the α-synucleinopathies like Parkinson’s disease (PD). Neurofilament light chain (NfL) have been reported to be higher in synucleinopathies as a sign of neurodegeneration. Objective: To evaluate whether plasma NfL is valuable in reflecting cognitive and motor status in iRBD and PD with a premorbid history of RBD (PDRBD), and predicting disease progression in iRBD. Methods: Thirty-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…[38] Another study reported that higher baseline NfL levels in patients with idiopathic RBD was associated with worsening cognitive, motor, and autonomic functions and a higher risk of phenoconversion. [11] The present study demonstrated that plasma NfL levels were significantly elevated in the PD, DLB, and high-risk groups compared with those in the low-risk group. In patients with PD, those classified as N+ had worse scores on the MoCA-J, Hoehn and Yahr, MDS-UPDRS III, SCOPA-AUT, BDI-II, PDQ-39, and QUIP scales than those classified as N−, suggesting that plasma NfL levels are related to cognitive function, and motor and non-motor symptoms.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…[38] Another study reported that higher baseline NfL levels in patients with idiopathic RBD was associated with worsening cognitive, motor, and autonomic functions and a higher risk of phenoconversion. [11] The present study demonstrated that plasma NfL levels were significantly elevated in the PD, DLB, and high-risk groups compared with those in the low-risk group. In patients with PD, those classified as N+ had worse scores on the MoCA-J, Hoehn and Yahr, MDS-UPDRS III, SCOPA-AUT, BDI-II, PDQ-39, and QUIP scales than those classified as N−, suggesting that plasma NfL levels are related to cognitive function, and motor and non-motor symptoms.…”
Section: Discussionsupporting
confidence: 53%
“…[6, 7] In addition, plasma neurofilament light chain (NfL) is regarded as a reliable biomarker for various neurodegenerative diseases. [8] Although recent studies have examined AD-related plasma biomarkers in patients with PD and DLB [9, 10] and plasma NfL in patients with idiopathic RBD,[11, 12] a detailed study on AD comorbidity in the prodromal phase of LBD is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A biomarker is a measurable characteristic indicating normal or pathogenic biological processes or pharmacological responses to therapeutic drugs (Miglis et al, 2021). Biomarkers used for diagnosis of and fMRI), and genetic biomarker (GBA variants, SNCA, TMEM175) (Bramich et al, 2022;Gnarra et al, 2023;Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A biomarker is a measurable characteristic indicating normal or pathogenic biological processes or pharmacological responses to therapeutic drugs (Miglis et al., 2021 ). Biomarkers used for diagnosis of iRBD patients include neurophysiological (polysomnography, actigraphy, electroencephalogram), clinical (hyposmia, cognitive dysfunction, visual dysfunction, motor function, autonomic function) and biological biomarker (blood test, CSF, tissue biopsy), neuroimaging (positron emission tomography [PET], single‐photon emission computed tomography [SPECT], structural magnetic resonance imaging [MRI], DWI and fMRI), and genetic biomarker (GBA variants, SNCA, TMEM175) (Bramich et al., 2022 ; Gnarra et al., 2023 ; Zhang et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…This prospective and longitudinal study provides an extra level of confidence and moves the field forward in the role of NfL as a supportive biomarker in the diagnosis of MSA, which has been recently added to the 2022 Movement Disorder Society criteria [6]. This may be particularly helpful in patients in the prodromal stages of disease, such as those with rapid eye movement (REM) sleep behavior disorder (RBD) and pure autonomic failure (PAF) [7,8]. However, other studies have also reported high NfL-c levels in patients with progressive supranuclear palsy (PSP) [9,10], and to a lesser extent in dementia with Lewy bodies (DLB) [11,12], which could represent up to 30% of MSA misdiagnosis in autopsy series [13,14].…”
mentioning
confidence: 99%